Changes in vitamins and trace elements after initiation of highly effective CFTR modulator therapy in children and adults with cystic fibrosis - a real-life insight - Dorit Fabricius; Tina Knieling; Noelle Zurmuehl; Leandra Makedon; Joachim Freihorst; Hanna Schmidt; Sebastian Bode (SpringerOpen, 2024)
Abstract Background Highly-effective CFTR-modulator therapy with elexa-/teza-/ivacaftor (ETI) has led to improvements in pulmonary outcomes, sweat chloride, body mass index (BMI) and quality of life in people with cystic fibrosis (CF). Improved uptake of fat-soluble vitamins and micronutrients has been reported for CFTR-modulators but data regarding ETI therapy is lacking. Methods This single-center retrospective study evaluated forced expiratory volume in one second (FEV-1), sweat chloride, BMI, transaminases (AST, ALT), bilirubin, vitamins A, D, E, zinc and selenium in children and adults eligible for ETI. Parameters were assessed before and up to one year after initiation of ETI. Results 58 patients (median age m = 28 years, SD ± 11.6 years, 51.7% female14 < 18 years old) were included. FEV-1 and sweat chloride improved significantly after ETI. There were no changes in BMI or AST. ALT was increased significantly after 4 weeks of ETI but returned to normal levels in further course. Bilirubin levels remained elevated after ETI. Vitamin A was significantly higher 12 months after ETI. No changes were found for vitamins D, E, zinc and selenium. Conclusions This study adds to the evidence that improvements of some fat-soluble vitamin levels can be found after ETI. No changes regarding micronutrients were noted. Individualized follow-up and supplementation are recommended.